Morphometrics of 39 fishes from the Seychelles artisanal fisheries. (18th December 2020) - Bodin, Nathalie; Govinden, Rodney; Souffre, Andrew; Adam, Pierre-André; Morgan, Matthew; Collier, Tom; Appoo, Jennifer; Burt, April J.; Sanchez, Cheryl; Fleischer-Dogley, Frauke; Chassot, Emmanuel
Abstract: A total of 5478 fishes were sampled between 2009 and 2020 to assess length–weight, length–length and weight–weight relationships in 39 marine species from 10 families caught in the Seychelles waters by the artisanal fishery. Two types of length (total length TL, fork length FL) and three types of weight (whole weight WT, gutted weight GW and gilled-gutted weight GGW) were measured. The parameters of the relationships were estimated using the log-transformed allometric model with bias correction. Our results include length–weight, length–length and weight–weight relationships for 39, 20 and 18 species, respectively. Our length–weight data and resulting relationships were compared against FishBase database for 36 species and were in the Bayesian 95% confidence interval of the relationships available for 33 species and above for Gnathanodon speciosus, Lutjanus gibbus and Variola louti . Finally, for five abundant and widely dispersed species we tested for spatial differences in morphometric relationships between the Mahé Plateau and three southern atoll groups. Significant differences were found for two species only, but their magnitude was small. We thus argue for the regression relationships based on pooled data to be used for most types of population and community analyses. The availability of these morphometric relationships will support the application of accurate size-based analyses for Seychelles fisheries survey data, and so enhance understanding of the ecology of the reef-associated fish component of marine ecosystems and food webs, and improve fisheries research management.